Students Reading Competence For Detail Information In Expository Text - Nurteteng, Nurteteng; Nopitasari, Dewi; Sumarji, Sumarji (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2019)
The purpose of this reseach to know how the students competence on their reading comprehension especially their ability in getting detailed information in expository text. The population of this research is 10 students of class X Akutansi SMK Modellink Makbusun. The research used descriptive analysis design. The instrument of this research was the reading test which focused on detail information in expository text. The result of students competence in getting detail information in expository text was 60% or 6 students got score among 70-100 and it was catagorized into good score. The other students or 2 students got in catagorized at “poor” catagory. The average of score students was 71.6. The competence of students in getting information in expository text was catagorized into “good” category.